Assessment of MODIS Surface Temperature Products of Greenland Ice Sheet Using In-Situ Measurements - Xiaoge Yu; Tingting Wang; Minghu Ding; Yetang Wang; Weijun Sun; Qinglin Zhang; Baojuan Huai (Land, 2022)
Satellite-based data have promoted the research progress in polar regions under global climate change, meanwhile the uncertainties and limitations of satellite-derived surface temperatures are widely discussed over Greenland. This study validated the accuracy of ice surface temperature (IST) from the moderate-resolution imaging spectroradiometer (MODIS) over the Greenland ice sheet (GrIS). Daily MODIS IST was validated against the observational surface temperature from 24 automatic weather stations (AWSs) using the mean bias (MB), the root mean square (RMSE), and the correlation coefficient (R). The temporal and spatial variability over the GrIS spanning from March 2000 to December 2019 and the IST melt threshold (−1 °C) were analyzed. Generally, the MODIS IST was underestimated by an average of −2.68 °C compared to AWSs, with cold bias mainly occurring in winter. Spatially, the R and RMSE performed the better accuracy of MODIS IST on the northwest, northeast, and central part of the GrIS. Furthermore, the mean IST is mainly concentrated between −20 °C and −10 °C in summer while between −50 °C and −30 °C in winter. The largest positive IST anomalies (exceeds 3 °C) occurred in southwestern GrIS during 2010. IST shows the positive trends mainly in spring and summer and negative in autumn and winter.